2013
DOI: 10.1200/jco.2013.31.15_suppl.2021
|View full text |Cite
|
Sign up to set email alerts
|

A large prospective Italian population study (Project of Emilia-Romagna Region in Neuro-Oncology; PERNO) in newly diagnosed GBM patients (pts): Outcome analysis and correlations with MGMT methylation status in the elderly population.

Abstract: 2021 Background: The role of temozolomide concurrent with and adjuvant to radiotherapy (RT/TMZ) in elderly pts with GBM remains unclear. We therefore evaluated the efficacy of this approach in pts >70 years in the context of the Project of Emilia-Romagna Region in Neuro-Oncology (PERNO), the first Italian prospective observational population-based study in neuro-oncology. Methods: The criteria for selecting pts enrolled in the PERNO study were: age >70 years; PS 0-3; histologically confirmed GBM; postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…With the above eligibility criteria, 16 studies [20] [35] were identified (2 phase III trials [24] [25] , 3 phase II trials [26] , [31] , [33] , 4 prospective cohort studies [22] – [23] , [34] – [35] and 7 retrospective cohort studies [20] – [21] , [27] – [30] , [32] ; Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the above eligibility criteria, 16 studies [20] [35] were identified (2 phase III trials [24] [25] , 3 phase II trials [26] , [31] , [33] , 4 prospective cohort studies [22] – [23] , [34] – [35] and 7 retrospective cohort studies [20] – [21] , [27] – [30] , [32] ; Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Of those, 4 studies [20] – [22] , [35] were published in abstract. Characteristics of the identified studies were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations